2014
DOI: 10.4103/0022-3859.143973
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent malignant proliferating trichilemmal tumor with lymph node metastasis in a young woman

Abstract: Malignant proliferating trichilemmal tumor (MPTT) is a rare cutaneous tumor predominantly affecting the scalp, eyelids, neck and face of elderly women. It is a large, solitary, multilobulated lesion that may arise within a pilar cyst. These tumors are largely benign, often cystic, and are characterized by trichilemmal keratinization. However, at times, the tumor has an aggressive clinical course and a propensity for nodal and distant metastases. Wide local excision with a 1 cm margin of normal tissue is the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 5 publications
2
6
0
1
Order By: Relevance
“…This is while some report metastasis and recurrence of malignant PTT. 15 , 16 The results of Table 2 also show that the majority of malignant PTT, at sites other than head and neck, have undergone surgical excision with wide margins (1–2 cm) without adjuvant therapy, which is similar to the treatment performed in the present study. But we cannot definitely state that this treatment is appropriate for this type of neoplasm, as most studies have not reported the long‐term outcome of the patients or have only reported 3–6 months' follow‐up results.…”
Section: Discussionsupporting
confidence: 79%
“…This is while some report metastasis and recurrence of malignant PTT. 15 , 16 The results of Table 2 also show that the majority of malignant PTT, at sites other than head and neck, have undergone surgical excision with wide margins (1–2 cm) without adjuvant therapy, which is similar to the treatment performed in the present study. But we cannot definitely state that this treatment is appropriate for this type of neoplasm, as most studies have not reported the long‐term outcome of the patients or have only reported 3–6 months' follow‐up results.…”
Section: Discussionsupporting
confidence: 79%
“…Adjuvant radiotherapy is widely used in case of metastases or local recurrence besides re-excision. Dubhashi et al administered 42 Gy in 21 sessions throughout one month due to lymph node involvement [ 42 ]. Not all patients are good surgical candidates; neoadjuvant therapy can be used with complete response in some cases.…”
Section: Tumors With Follicular Differentiationmentioning
confidence: 99%
“…There is a paucity of information on the non-surgical management of MPTT (Table 2). 2,69,12,13,15,16,2024,44,58–61 The few studies that do exist have shown: that ethanol injections may be useful for local recurrence; that chemotherapy regimens containing cisplatin, doxorubicin, and vinca alkaloids can be beneficial for metastatic disease; and that radiotherapy can be effective in preventing primary lesion recurrence. Here, we show that metastatic MPTT can be responsive to a variety of chemotherapy regimens and a small molecule inhibitor of PI3K, in the setting of a somatic PIK3CA activating mutation (Fig.…”
Section: Discussionmentioning
confidence: 99%